Analisis Pengaruh Karakteristik Hujan terhadap Gerakan Lereng - Haryanti, Sri; Suryolelono, Kabul Basah; Jayadi, Rachmad (Jurnal Semesta Teknika, 2010)
Soil movement mostly occurs especially during rainy season at the slope of Kalibawang irrigation channel at KM 15,9 in Kulon Progo district, Daerah Istimewa Yogyakarta. The slope movement causes damage at the school building, bridge and irrigation channel. Based on this fact, a research is necessary by modeling the slope at site of conducted. The objectives of this research are to identify the rainfall characteristic which triggering slope movement and to recognizes factor affecting the slope movement. Topography data, physical characteristic, and soil mechanic were applied as the input simulation models. Groundwater flow in slope was numerically simulated by using SEEP/W while the slope deformation simulated by SIGMA/W. Both SEEP/W and SIGMA/W were applied simultaneously in the numerical simulation. Rainfall design with appropriate return period was determined from rainfall annual daily maximum historical data recorded from 1985-2004, while distribution was completed by applying statical analysis on hourly rainfall data. The analysis of normal daily rainfall was determined based on daily rainfall data from Kalibawang rain gauge. Six models were applied as follow: initial condition (Rainfall Model I), heavy rainfall in short duration (Rainfall Model II), normal daily rainfall of 25 and 40 mm in long duration (Rainfall Model III), normal daily rainfall of 20 mm in long duration (Rainfall Model IV), heavy rainfall followed with normal daily rainfall of 20 mm (Rainfall Model V) and normal rainfall of 20 mm followed with heavy rainfall (Rainfall model VI). The result shows that at the research location, the maximum daily rainfall of 2-year-return period is 113,8 mm with dominant duration was 4 hour per day. This value was applied as Rainfall Model II. Based on the simulation the movement or deformation with Rainfall Model II, III, IV, V and VI is 0,22 m; 0,956 m; 1,01 m, ; 0,652 m, and 0,568 respectivally. It is concluded that at the research location, heavy rainfall in short duration gives small impact to slope movement or slope deformation and normal rain of 20 mm in long duration (Rainfall Model IV) is highly significant to the slope movement or slope deformation.